Energy dissipation in open channels by large semi-circular disk roughness elements - Charng, Der-ruenn; Ackermann, Norbert L.; Flammer, Gordon H.; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1969)
The study of flow resistance in very steep and rough open channels has direct application to many streams in the upper regions of a drainage basin. Steep channels, causing a high gradient flow in a very rough channel, also provide a means of using large roughness elements for energy dissipation. Flume tests were conducted using semi-circular disks as roughness elements. The disks were made of aluminum sheets. The relative depths investigated ranged from approximately 1 to 6. From the experimental results, no meaningful relationships could be found between the flow resistance C/ {u221A} g, the relative depth y/k and geometric parameters describing the channel shape. This indicated that other variables such as air entrainment and the Froude number of the flow, which were originally not considered to be significant, were important in describing the flow phenomenon.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1969
Keywords: Hydraulics